1988
DOI: 10.1002/ps.2780240102
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic hydrolysis of quinalphos on homoionic clays

Abstract: The decomposition of quinalphos, O,O‐diethyl O‐quinoxalin‐2‐yl phosphorothioate, on homoionic Cu(II)‐, Fe(III)‐, Al‐, Na‐, K‐ and Cabentonites in hydroalcoholic solution has been investigated. The results show that the hydrolysis of the pesticide may involve two different mechanisms, both depending on the nature of the exchangeable cations. The pesticide hydrolyses to 2‐hydroxyquinoxaline on the Cu‐, Fe‐ and Al‐clays, whereas O‐ethyl O‐quinoxalin‐2‐yl thiophosphoric acid is the main product of hydrolysis on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Because of their favourable physical and chemical properties, such as high surface area, large adsorption and ion-exchanging capacity, montmorillonites are widely employed as catalysts in the synthesis of fine chemicals and drugs under mild experimental conditions. [9][10][11][12][13][14][15][16][17] Remarkably, montmorillonites catalyze the aldol condensations of formaldehyde into sugars ("formose reaction"). [18,19] From these points of view montmorillonites can be considered as primitive enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their favourable physical and chemical properties, such as high surface area, large adsorption and ion-exchanging capacity, montmorillonites are widely employed as catalysts in the synthesis of fine chemicals and drugs under mild experimental conditions. [9][10][11][12][13][14][15][16][17] Remarkably, montmorillonites catalyze the aldol condensations of formaldehyde into sugars ("formose reaction"). [18,19] From these points of view montmorillonites can be considered as primitive enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…One of them is derivatization of the herbicides into less harmful compounds after crop development while the other is the metal ion associated degradation or deactivation of the herbicides [5][6][7][8]. Studies have shown that metal ions can show remarkable effect in catalyzing the decomposition of herbicides [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Various reviews emphasize the role played by the clay surfaces in catalyzing the hydrolysis of organic pollutants (Ortego et al 1991;Kowalska et al 1994). The saturating cation is critical to the catalytic effect, since upon changing the nature of the cation associated with the clay, different hydrolysis rates and pathways are observed (Saltzman et al 1974;Pusino et al 1988;Pusino and Gessa 1990;Pusino et al 1993). Sulfonylureas are also strongly adsorbed (Ukrainczyk and Rashid 1995) and degraded on smectites (Pantani et al 1994).…”
Section: Introductionmentioning
confidence: 99%